2018
DOI: 10.1159/000489489
|View full text |Cite
|
Sign up to set email alerts
|

Doctors’ Knowledge and Attitudes Regarding Enteral Feeding and Eating Problems in Advanced Dementia

Abstract: Background: The use of feeding tubes (FTs) in patients with advanced dementia does not yield positive health outcomes and can have a negative effect. Methods: A cross-sectional study assessed the knowledge and attitudes of physicians on the use of FTs for patients with advanced dementia. Results: 201 of 240 doctors (83.8%) participated in the study; 61.7% of the doctors claimed that FTs prevent aspiration, 51.7% that they prevent pneumonia, and 38.8% that they prevent weight gain. Almost one-third (32.3%) said… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 45 publications
0
14
1
Order By: Relevance
“…e benefit of tube feeding in reducing aspiration pneumonia occurrence is further reinforced by recent survey of doctors' knowledge and attitudes about tube feeding in latestage dementia. e survey reveals that 61.7% of the doctors claimed tube feeding prevents aspiration and more than half (51.7%) of the participants believed tube feeding prevents pneumonia [101]. e latter findings bolster the result of an earlier survey involving 195 primary care physicians in the United States that claimed PEG feeding of individuals with advanced dementia provides a range of benefits; 76% of the physicians agreed that PEG feeding reduce aspiration pneumonia and 61% of them believed it prolongs survival [74].…”
Section: Aspiration Pneumonia Incidence a Study Of Elderlymentioning
confidence: 66%
“…e benefit of tube feeding in reducing aspiration pneumonia occurrence is further reinforced by recent survey of doctors' knowledge and attitudes about tube feeding in latestage dementia. e survey reveals that 61.7% of the doctors claimed tube feeding prevents aspiration and more than half (51.7%) of the participants believed tube feeding prevents pneumonia [101]. e latter findings bolster the result of an earlier survey involving 195 primary care physicians in the United States that claimed PEG feeding of individuals with advanced dementia provides a range of benefits; 76% of the physicians agreed that PEG feeding reduce aspiration pneumonia and 61% of them believed it prolongs survival [74].…”
Section: Aspiration Pneumonia Incidence a Study Of Elderlymentioning
confidence: 66%
“…In another cross-sectional survey of six long-term geriatric hospitals in Israel and Canada, the rate of tube feeding in patients with end‐stage dementia was 24% (92/2287), although there was a lower prevalence of feeding tube use in Canadian institutions than in Israeli hospitals [9]. In Israel, a study found knowledge gaps amongst physicians pertaining to feeding tube indications [10]. In Japan, the provision of artificial nutrition and hydration has been long considered standard care even in individuals with severe cognitive impairment due to multiple reasons including, and not limited to the national health insurance system that allows elderly patients to become long-term hospital in-patients, legal and emotional barriers with regard to limiting treatment options, the risk of prosecution, cultural barriers, all promoting PEG placement [11].…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, enteral (rather than parenteral) nutrition is recommended in a wide range of clinical situations, including organ transplantation [11], cancer [29], pancreatitis [3,30], Crohn's disease [31], intestinal resection or inflammation [5], critical disease [3,6,7,9], and the postoperative period [3,8,11,23]. It is also preferred for premature or low-birth-weight infants [12,32], for the elderly, for neurological patients [29,[33][34][35], for patients with anorexia nervosa [29], and for those with AIDS [36]. Nevertheless, enteral nutrition is not free of drawbacks, as discussed below [1,22].…”
Section: Enteral Versus Parenteral Nutritionmentioning
confidence: 99%
“…However, regardless of their disease, patients on enteral nutrition often show a series of "secondary" symptoms that can be described as gastrointestinal tract reactions to diet administration, including: pain, discomfort, gastric residual volume, delayed gastric emptying, abdominal bloating and cramps, nausea/vomiting, diarrhea [1,4,8,9,12,20,22,32,[33][34][35][36][37][38][39], metabolic disorders [1,12], and, when the enteral nutrition is longer term, ulcers and major weight loss [33,34]. In addition, some patients are unable to tolerate enteral nutrition [9,22], especially pediatric patients [38,39].…”
Section: Problems Associated With Enteral Nutritionmentioning
confidence: 99%